The Interview Times : Fariz İsmailzadə | Buraxılış No.5 | May, 2022 - El Presidente; Kamanga, Nathan; Namazova, Fidan; Eyvazova, Fəridə; Bayramov, Anar; Əsgərova, Suğra; Duran, Alejandra Garcia; Zeynallı, Nərmin (ADA University, 2022)
Müsahibənin tamamını oxumaq üçün aşağıda View/Open hissəni tıklayın.
Keywords: ADA University--Newspaper.